Family Day Care An ERIC Abstract Bibliography. - ERIC Clearinghouse on Early Childhood Education, Champaign, IL.; ERIC Clearinghouse on Elementary and Early Childhood Education (New York, NY : ERIC Clearinghouse on Urban Education, 1978)
This abstract bibliography cites recent ERIC documents and journal articles concerning family day care. Many entries also discuss other types of day care. Entries include resumes from Resources in Education (RIE), February 1976 through December 1977, and citations from Current Index to Journals in Education (CIJE), September 1976 through December 1977. Additional references to books, periodicals and audiovisual materials related to family day care but not available through ERIC are listed at the end of this bibliography. (Author/BD)
Availability: ERIC Clearinghouse on Early Childhood Education, University of Illinois, 805 West Pennsylvania Avenue, Urbana, Illinois 61801 (Catalog #172, $2.00).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: 400-78-0008.
ERIC Note: Not available in hard copy due to small print size.
Educational level discussed: Early Childhood Education.
May also be available online. Address as at 14/8/18
Keywords: Ancillary Services; Annotated Bibliographies; Child Care; Day Care; Day Care Centers; Early Childhood Education; Family Day Care; Infants; Parent Participation; Preschool Children; Program Descriptions; Reference Materials, Bibliographies